From goals to gains : a review of our 2022 performance indicator achievements / Muhammad Aiman Abdul Halim - Abdul Halim, Muhammad Aiman (Academy of Language Studies, 2023)
As of February 2023, all performance indicators for faculties and departments in UiTMCPP were finalized. The final report indicates that APB achieved a total performance indicator (PI) score of 70.1%, marking a significant milestone for us at Akademi Pengajian Bahasa (APB) UiTMCPP. Our journey has been challenging, but it has also been a valuable learning experience. Looking back at the year 2022, what lessons have we learned? Throughout 2022, our department was tasked with achieving a total of 19 PIs. As in previous years, APB staff were divided into four groups to brainstorm activities and strategies aimed at fulfilling these PIs. Thanks to the hard work of the group members, these discussions were a great success, resulting in a total of 54 planned activities for our department's strategic action plan. Of course, not all plans were realized due to the many obstacles we faced throughout the year. Nevertheless, we remained adaptable and resourceful, with some unplanned activities even contributing to our PI achievements.